Chemical recycling of polyethylene terephthalate waste into BHET monomer using convection-conductive and microwave assisted glycolysis techniques - Mhd. Adnan, Amir Syariffuddeen (2012)
Abundant amount of polyethylene terephthalate (PET) waste is becoming a serious problem in our country due to high consumption of various products such as softdrink bottle, food container, etc. The non-biodegradability of PET is the major obstacle to dispose this waste using conventional method such as landfilling and incineration, and thus causing impact to environment, economics and human health. Chemical recycling is one of the option that can be acceptable based on the principle of environmental sustainability, leading to the conversion of waste into the raw materials (monomers) from which the polymer itself is made. It has been reported to be effective for depolymerization of polyethylene terephthalate (PET) that can be carried out under mild condition of temperature 190°C and 1-2 MPa pressure, in which bis-2-hyrdroxyethyl terephthalate (BHET) monomer, can be easily produced. The objective of this study to further investigate the glycolysis reaction for depolymerization of PET waste into BHET monomer and also studies on heating mechanism using convection-conductive and microwave irradiation. Parameters affecting the glycolysis reaction being investigated, namely the effect of catalyst concentration (ratio PET:catalyst), solvent concentration (ratio EG:PET), glycolysis reaction time, reaction temperature and selection of catalysts. Zinc acetate is found to be the best catalyst compares to zinc chloride, sodium bicarbonate and titanium (IV) oxide. The optimal operating conditions for glycolysis has found at 196°C in 5:1 ratio PET:EG with 1.5% catalyst: PET ratio in the presence of zinc acetate catalyst in 8 hours reaction with conversion achieving 88% and 75% composition of BHET monomer. In microwave heating glycolysis, reaction at 196°C with 5:1 ratio EG:PET, 1.5% catalyst: PET, in 30 minutes of reaction time resulting a product conversion of 76% with 71% BHET. Characterization and identification of glycolysis products (GP) through physical, thermal and chemical analysis conclude that the main component in the GPs consist of bis 2-hydroxyethyl terephthalate (BHET) monomer together with other high chain oligomers and dimers. A comparison between different heating mechanism techniques reported that microwave heating has superior productivity in PET conversion with 8 times shorter time consumption than conventional heating method. It also provides positive result in the economical aspect with the production can reach 14 times higher with 40% cost and 32% energy consumption than that observed in the conventional heating technique.